A Critical Analysis of Patriarchal Constructs in Ibn Kathir’s Exegesis of Gender-Related Qur’anic Verses - Muhammad RIdwan; Basri Mahmud (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Qur’anic interpretation is not a neutral act; it is shaped by the socio-cultural and historical context of the exegete. These contextual factors significantly influence how interpreters understand and represent gender roles within Islamic teachings. This study critically analyzes the influence of patriarchal culture in classical tafsir by examining Ibn Kathir’s interpretation of three key verses concerning gender: Qur’an 4:34 (male authority over women), 2:282 (the legal testimony of women), and 4:11 (rules of inheritance). Employing a combination of exegetical analysis and a gender-critical approach, the research explores the extent to which patriarchal social structures are embedded in Ibn Kathir’s tafsir. The findings indicate that his interpretations tend to reflect a hierarchical view of gender, often positioning women as socially and legally subordinate to men, consistent with the dominant norms of his time. This study argues for the importance of reinterpreting Qur’anic texts through a contextual and justice-oriented lens that considers contemporary understandings of gender equality while remaining faithful to Islamic principles.